PROFESIONALISME GURU DALAM MENINGKATKAN KUALITAS PENDIDIKAN AGAMA ISLAM MELALUI PENILAIAN KINERJA GURU - Ubabuddin, Ubabuddin (At-Tuhfah : Jurnal Studi Keislaman, 2018)
The study of teacher professional development requires the seriousness of all elements of education, to achieve the goals of education, of course professional educators are needed. Professional educators are educators who have qualifications and conditions that must be mastered. A good teacher or educator is those who meet the requirements of professional skills as educators or as instructors or trainers. Herein lies the importance of the teacher's professional quality standards to ensure the teaching and learning process and quality learning outcomes. Improving the quality of teacher performance must always be pursued, one of which is through teacher quality assessments.